Effect of Contaminant on Breakdown Characteristics of Mineral Oil and Palm Oil - Maneerot, S.; Pattanadech, N. (My University, 2018)
This paper details an investigation of the effect of contaminant particles at several different temperatures on the 50 Hz AC breakdown voltage of two dielectric liquids - mineral oil and palm oil. The liquids in the test cell used were comprised of various combinations of the following: a) three particle types (cellulose, spherical iron and copper) of approximately 20 μm diameter, b) three contaminant concentrations i.e.0.001% m/V, 0.003% m/V and 0.005% m/V, and c) four liquid temperatures i.e. 25°C, 50°C, 70°C, and 90°C. were investigated with mushroom shaped electrodes in accordance with IEC 60156. The results obtained in this test process showed that the presence of the added particles in the tested dielectric liquids consistently provided a reduction in breakdown voltage, and that the reduction factor varied according to particle type, particle concentration, liquid type, and liquid temperature, and on whether they consisted of cellulose insulation material or copper and iron conducting material summarizing the test results, it was shown that higher contaminant concentration produced lower breakdown voltages, that the addition of copper particles had the most significant effect on reducing breakdown strength, and that the greatest reduction of breakdown strength was measured in the contaminated mineral oil test samples at a test temperature of 70°C.
Keywords: breakdown voltage; contaminant; mineral oil and palm oil